The Spatial Pattern of International Labour Flows from and to Pakistan: A Preliminary Analysis (The Pakistan Development Review, 1992)
Since the mid-1970s Pakistan has witnessed very high magnitudes of labour outand in-migration. Most of the earlier studies on the subject either concentrated on the aggregate macro-economic impact of this migration on the national economy or have been in the nature of case studies of specific' groups of migrants'. In these studies, the analysis of geographical distribution of the labour force has been missing. Given the fact that both out- and return-migrants may have location-specific effects which might lead to uneven economic and social development in the country and as such policies would have to respond in concrete locational terms. such an omission is critical. This paper attempts to identify the international labour flows of Pakistanis focussing on their geographical distribution. Based on a survey conducted by the Overseas Pakistanis Foundiition and the Population Census of 1981 the study suggests that less developed districts are characterised by low out-migration and high return-migration. In addition, structural characteristics (e.g .• land tenure) may be important in explaining low mobility from some underdeveloped districts. e.g., those of Sindh and lower Punjab. On the basis of the information presented. the paper suggests a nurnber of avenues for future research: (i) to relate the indices of out- and return-migration to disaggregated characteristics of the regional socio-economic structure; (ii) to compare the pattern of international out-migration with the pattern of internal out-migrant; (iii) to verify whether the process of internal relocation is of significant magnitude a trace analysis of return migrants to the less developed districts could be attempted; and (iv) to determine the socio-economic and political implications of the patterns of out- and return-migration. as the differential patterns are likely to have significant implications for future development.